2009
DOI: 10.3109/00016480903380539
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of a system for the automated recording and analysis of electrically evoked compound action potentials (ECAPs) in cochlear implant patients

Abstract: The time required to determine a TECAP threshold for a single electrode contact was found to be between 0.5 and 1 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
0
13
0
2
Order By: Relevance
“…Second, as the minimum age for implantation continues to decrease while the inclusion criteria continue to expand, the psychophysical test may be challenging or even impossible for the pediatric and expanded populations. The objective physiological measure is relatively reliable, fast and requires no subjective responses, which makes it useful to not only predict threshold and maximal loudness, but also spatial selectivity in cochlear implants (e.g., Eisen et al, 2004; Gartner et al, 2010). Combining these physiological measures could allow efficient and effective fitting of the cochlear implant and improve its overall performance.…”
Section: Discussionmentioning
confidence: 99%
“…Second, as the minimum age for implantation continues to decrease while the inclusion criteria continue to expand, the psychophysical test may be challenging or even impossible for the pediatric and expanded populations. The objective physiological measure is relatively reliable, fast and requires no subjective responses, which makes it useful to not only predict threshold and maximal loudness, but also spatial selectivity in cochlear implants (e.g., Eisen et al, 2004; Gartner et al, 2010). Combining these physiological measures could allow efficient and effective fitting of the cochlear implant and improve its overall performance.…”
Section: Discussionmentioning
confidence: 99%
“…We envisage a closed-loop CI which can automatically accesses and analyze neural responses from multiple levels in the auditory neural pathway. First, the ECAP and EABR responses [20], [64] could be used in a closed-loop CI to automatically set the comfort and threshold levels, eliminating a tedious job for the audiologist [17]. However, further work is still needed to find a completely automated and method of estimating behavioral thresholds from ECAP and EABR responses.…”
Section: B Applications For the Eer Techniquementioning
confidence: 99%
“…To design a completely closed-loop CI system it would be necessary to record and analyze EP responses automatically. Recently, an important study [17] has shown that automated collection and analysis of ECAP responses is feasible, reliable and repeatable. We envisage a closed-loop CI which can automatically accesses and analyze neural responses from multiple levels in the auditory neural pathway.…”
Section: B Applications For the Eer Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…In this way, verification of an auditory response is obtained as well as some level of confirmation of device function, and response characteristics can be useful in the setting of processor fitting parameters, particularly in young children who are unable to provide reliable behavioural responses [6,16]. Because of the evolved state of this method and its automatic determination of the neural responses [18], the method has gained broad clinical application in this patient group. In addition, eCAP measures are able to identify certain electrode anomalies, although the amount of direct information is limited.…”
Section: Introductionmentioning
confidence: 99%